Consumer Spending and the Economic Stimulus Payments of 2008 - Parker, Jonathan A; Souleles, Nicholas S; Johnson, David S; McClelland, Robert (American Economic Review, 2013)
We measure the change in household spending caused by receipt of the economic stimulus payments of 2008, using questions added to the Consumer Expenditure Survey and variation from the randomized timing of disbursement. Households spent 12–30 percent (depending on specification) of their payments on nondurable goods during the three-month period of payment receipt, and a significant amount more on durable goods, primarily vehicles, bringing the total response to 50–90 percent of the payments. The responses are substantial and significant for older, lower-income, and home-owning households. Spending does not vary significantly with the method of disbursement (check versus electronic transfer). (JEL D12, D14, E21, E62)